APLIKASI PENCARIAN LOKASI AGEN TIKI (TITIPAN KILAT) DI YOGYAKARTA UNTUK ANDROID - Suharto, Untoro Hadi; Triyono, Joko; Sutanta, Edhy (Jurnal Script, 2014)
ABSTRACTTIKI (express courier) is a domestic and international delivery service. TIKI itself already has a system which is running, it is a dynamic website system that can only be run by using the internet browser. Currently, the androidâs operating system open source is growing rapidly and rising in popularity for competing bravely with other mobile operating systems such as ios, blackberry or windows phone. As the result, it encourages the android operating system to maximize its potential by creating a GPS (Geographic Positioning System) app like Google Maps to detect TIKIâs agent locations in Yogyakarta. The application is expected to facilitate TIKI users when opening the website, because the application can be run in mobile devices with android operating system.This application is expected to help users in tracking the package which has shipped with receipt number, by using receipt checking feature. The nearest from TIKI feature is a feature that can show the nearest route from the TIKI agent location and display where the location exactly is, with the blue marker appeared in maps.The aplication for TIKIâs agent location search is created by using the programming language PHP and a MySQL database processing. Eclipse software also contributes the application because it requires the Java programming language, thus, the application can be implemented on mobile devices with Android based.